Identifikasi Sakarin Dalam Sediaan Jamu Pelancar Haid Yang Beredar Di Pasar Kota Klaten - Dhiyan Chahyaningrum (Jurnal Medika Nusantara, 2023)
Saccharin is a synthetic chemical substance that is classified as a food or beverage additive. Menstrual facilitating herbs are often consumed by women when they are menstruating, and this would be a bad thing if these herbs contain saccharin. One of the variations of menstrual facilitating herbal medicine that is often consumed is tamarind turmeric. The content of saccharin that is routinely consumed can cause a person to experience metabolic dysfunction. This study aims to look at the characteristics and determine the levels of saccharin in menstrual-promoting herbal preparations circulating in the Klaten City Market. This research is a type of experimental descriptive research. This study used the method of color test, TLC, and FTIR Spectroscopy. The results showed that of the 10 samples of herbal medicine to facilitate menstruation which were analyzed by the Iron (III) Chloride Test and the Absorbinol Test, no saccharin was found. In the Thin Layer Chromatography (TLC) Test, there were no stains or Rf which were the same or almost close to the Rf of the comparator standard for saccharin artificial sweeteners. From the results of the analysis, it can be concluded that of the 10 samples of menstrual-launching herbs that were examined, they were negative for the artificial sweetener saccharin.